Correlation of HbA1c levels with Triglyceride, LDL and HDL levels in Type 2 Diabetes Mellitus Patients - Tri Prasetyorini; Cindy; Salbiah (International Journal of Science and Society, 2021)
Diabetes mellitus (DM) is a group of metabolic diseases with characteristics of increased blood glucose levels that occur due to abnormal insulin secretion, insulin action or both. It is necessary to monitor long-term glycemic status by measuring HbA1c levels to determine the quality of long-term blood glucose control. People with Type 2 DM are more at risk of suffering from cardiovascular disease characterized by dyslipidemia, with a characteristic description of high plasma triglyceride levels, elevated LDL levels and decreased HDL levels. The purpose of this study was to determine the relationship between HbA1c levels and levels of triglycerides, LDL and HDL. This study was an analytic observational study using a cross-sectional design. Data on each variable is secondary data obtained from patients with Type 2 DM at Jakarta Friendship Hospital for the period January-December 2018. The research sample used was 97 data of Type 2 DM patients. Chi-Square test showed an association between HbA1c levels and triglyceride levels with a value of p = 0.046 (< 0.05), there was a relationship between HbA1c levels and LDL levels with p = 0.742 (p > 0.05), and there was a relationship between HbA1c levels and HDL levels with p = 0.241 (p > 0.05). The conclusion obtained in this study is that there is a significant relationship between HbA1c levels and triglyceride levels and there was no significant relationship between HbA1c levels and LDL and HDL levels.